Health-related quality of life and its determinants among patients with psoriasis at a referral hospital in Northwest Ethiopia - Belachew, Eyayaw Ashete; Chanie, Gashaw Sisay; Gizachew, Eshetie; Sendekie, Ashenafi Kibret (Frontiers in Medicine, 2023)
Objectives This study assessed health-related quality of life (HRQoL) and its determinants among patients with psoriasis having follow-ups at the University of Gondar Comprehensive Specialized Hospital (UoGCSH). Design, setting, and participants A cross-sectional institutional-based study was conducted at the dermatologic clinic of UoGCSH from June to August 2022. Four hundred eligible patients with psoriasis were included in the study using a systematic random sampling technique. The main outcome measured The Dermatology Life Quality Index (DLQI) measurement scale was used to assess HRQoL. The relationship between HRQoL and independent predictor variables was investigated using bivariable and multivariate logistic regression analyses. Statistical significance was defined as a p-value of <0.05 at the 95% CI. Results Of the 422 study subjects approached, 400 respondents with psoriasis were included in the final analysis. The mean (±SD) age was 39.8 (±17.2) years, and 56% were women. The most commonly prescribed medications were topical corticosteroids (68.3 %). The mean (±SD) DLQI was 13.05 (7.82). More than three-fourths (78.5%) of the patients' HRQOL was affected, and its severity ranged from very large to extremely large. Being male (adjusted odd ratio) (AOR) = 0.373, 95% CI (0.171, 0.773), the use of alternative therapy (AOR) = 0.237, 95% CI (0.114, 0.494), duration of diseases (AOR) = 0.184, 95% CI (0.061, 0.557), duration on medication (AOR) =3.75, 95% CI (1.32, 10.73), presence of comorbidity (AOR) = 6.199, 95% CI (1.921, 20.00), and income were found to have a significant association with poor HRQoL. Conclusion Psoriasis patients had reduced HRQoL, which was lower than that of the normal population. The study identified that several variables contributed to this reduced HRQoL. Predictors that take into account interventions were essential for preserving patients' HRQoL.